GENDER DISCRIMINATION AGAINST WOMEN IN BINA SHAH’S BEFORE SHE SLEEPS: A REVIEW ON THE MAIN CHARACTER - Firliana Alvira; Ni Made Widisanti S; Agnes Setyowati (Universitas Pakuan, 2021)
The main topic in this research is gender discrimination which is based on the study of the main character in Bina Shah's Before She Sleeps. This research process involves the whole story, intrinsic elements: characters and characterizations, settings, and conflicts, as well as extrinsic elements: gender discrimination, patriarchy systems, and power relations. This qualitative research is supported by descriptive analysis methods and literature study techniques which result in findings that politicized gender disparities are the cause of gender discrimination. The main character, Sabine, experiences several forms of gender discrimination namely limited access to education and not allowed to work. Her only choice is to be a good housewife with three to five husbands, and to bear as many children as possible. This system, prompting Sabine to put up resistance by running away.Keywords : gender; gender discrimination; gender gap; patriarchy system; main character